Beetle pollination and flowering rhythm of Annona coriacea Mart. (Annonaceae) in Brazilian cerrado: Behavioral features of its principal pollinators - Costa, Marilza Silva; Silva, Ricardo José; Paulino-Neto, Hipólito Ferreira; Pereira, Mônica Josene Barbosa (Plos One, 2017)
The conservation and sustainable management of Annona coriacea requires knowledge of its floral and reproductive biology, and of its main pollinators and their life cycles. In this work, we analyzed these aspects in detail. Floral biology was assessed by observing flowers from the beginning of anthesis to senescence. The visiting hours and behavior of floral visitors in the floral chamber were recorded, as were the sites of oviposition. Excavations were undertaken around specimens of A. coriacea to determine the location of immature pollinators. Anthesis was nocturnal, starting at sunset, and lasted for 52–56 h. The flowers were bisexual, protogynous and emitted a strong scent similar to the plant´s own ripe fruit. There was pronounced synchrony among all floral events (the period and duration of stigmatic receptivity, release of odor, pollen release and drooping flowers) in different individuals, but no synchrony in the same individuals. All of the flowers monitored were visited by beetle species of the genera Cyclocephala and Arriguttia. Beetles arrived at the flowers with their bodies covered in pollen and these pollen grains were transferred to the stigmata while foraging on nutritious tissues at the base of the petals. With dehiscence of the stamens and retention within the floral chamber, the bodies of the floral visitors were again covered with pollen which they carried to newly opened flowers, thus promoting the cycle of pollination. After leaving the flowers, female beetles often excavated holes in the soil to lay eggs. Larvae were found between the leaf litter and the first layer of soil under specimens of A. coriacea. Cyclocephala beetles were the main pollinators of A. coriacea, but Arriguttia brevissima was also considered a pollinator and is the first species of this genus to be observed in Annonaceae flowers. Annona coriacea was found to be self-compatible with a low reproductive efficiency in the area studied. The results of this investigation provide ecological data that should contribute to the conservation and economic exploitation of A. coriacea.
Keywords: Brazilian cerrado; Beetle pollination; Flowering rhythm